Analysis and reduction of wrinkling defects for tube-hydroforming magnesium alloy components at elevated temperatures. (5th July 2019) - Kong, T.F.; Lu, X.Z.; Chan, L.C.
Abstract: Wrinkling defects commonly occur in tube hydroforming (THF) magnesium (Mg) alloy at elevated temperatures when the tube-end and axial-feeding regions of the workpiece are overheated. Most previously proposed methods for preventing such defects have been applied at room temperature and restricted by several limitations. Therefore, this paper presents a breakthrough in tool design through the appropriate control of temperature distribution of the Mg alloy AZ31B tubular material to minimise the wrinkling defects in THF at evaluated temperatures. The proposed cost-effective, simple and user-friendly collet-type device design was able to provide a non-isothermal condition for THF within an appropriate pre-heating time after die closing. An axisymmetric barrel-shaped component was taken as a prime example to demonstrate the methodology, in which various thermal potential differences between the axial-feeding and deformation regions were investigated using finite-element (FE) simulation so as to evaluate the wrinkling effects under various non-isothermal conditions. The results showed that the most satisfactory component could be obtained when the average temperatures of axial-feeding and deformation regions were around 240 and 330 °C, respectively. Subsequently, with the same approach, a wrinkle-free non-axisymmetric tubular bike-frame component was hydroformed successfully as a more realistic and practical application example. Graphical abstract: Unlabelled Image Highlights: A collet-type device was used to reduce wrinkling defects in tube-hydroforming of Mg alloy AZ31B at elevated temperatures. Effects of material temperature and properties on the wrinkling defects during tube-hydroforming were analysed theoretically. Effects of die-core temperature and pre-heating time on wrinkling occurrence and wall thinning were studied by FE simulation. The most satisfactory barrel-shaped component was hydroformed at die-core temperature ≈ 350 °C and pre-heating time ≈ 10 s. A subsequent wrinkle-free bike-frame component was hydroformed successfully using the same approach and proposed tool design.